PENGARUH MODEL PEMBELAJARAN PROJECT BASED LEARNING TERHADAP MOTIVASI BELAJAR MATEMATIKA SISWA SEKOLAH DASAR - Faisal Eka Mahendra; Sundari Sundari; Erni Enggelina Eregua; Arie Anang Setyo; Irna Rusani; Nika Fetria Trisnawati (Prima Magistra: Jurnal Ilmiah Kependidikan, 2023)
Education has an important role in the development of individuals and society. Mathematics is often considered difficult by students, requiring understanding concepts and applying formulas. The Project Based Learning (PjBL) Learning Model emerged as an effective alternative, enabling students to be involved in contextual mathematics projects. This study aims to investigate the effect of PjBL on the motivation to learn mathematics in SD Inpres 46 Sorong City students. The research method is an experiment with a one group pretest-posttest design. The sample is 20 grade 3 students of SD Inpres 46, Sorong City. The results showed a significant increase in students' motivation after the treatment. The distribution of pretest-posttest scores is close to the normal distribution. The reliability test shows the motivational questionnaire is reliable. The hypothesis test indicated a significant difference between pretest and posttest. Students learn through group work in completing assignments and making works, so they are more enthusiastic in learning. They pay full attention to the teacher's instructions and dare to ask and answer questions from the teacher. In addition, students also actively work together in completing assignments given by the teacher. Thus, this study succeeded in increasing student motivation through PjBL. These results can support the development of more effective learning strategies in the field of mathematics education at the elementary level. According to the results of calculating the average score on the learning motivation scale in the experimental group was 75.35, while the average posttest score on the learning motivation scale in the experimental class was 87.57.